Lifespan oxytocin signaling: maturation, flexibility, and stability in newborn, adolescent, and aged brain - Sannino, Sara; Chini, Bice; Grinevich, Valéry (Developmental neurobiology, 2017)
The hypothalamic neuropeptide oxytocin (OT) is a forefront molecule among neuropeptides due to its pronounced prosocial effects and its potential use in socioemotional deficits that characterize the most prevalent neurodevelopmental and psychiatric disorders (autism spectrum disorders and schizophrenia). The effects of OT have been studied in young and adult subjects (either animals or humans), while the complete lifespan trajectories of OT system development and activity have been far less investigated. In this (mini) review, we will primarily focus on three temporal distinct periods of life - early postnatal period, puberty/adolescence, and elderly. We selected the neonatal period to discuss the role of OT in the switch of GABA action from excitation to inhibition in the first days after birth (in rodents), with potential implications in neurodevelopmental disorders. In the puberty/adolescence period, we consider of particular relevance the OT impact on drug consumption, stress and aggression. Finally, OT could potentially contribute to maintain social capacities of aged people and to ameliorate socially emotional deficits and symptoms of neurodegenerative diseases.
Gesehen am 05.07.2018
Published online 7 September 2016